Formação continuada de professores : narrando memórias construímos sujeitos na escola e na vida - Bonifácio, Maria Acácia de Lima (2015)
This paper seeks to answer the relevance of video as an educational resource to collaborate with the educational activities of the Portuguese-speaking teachers aimed at raising writing skills of elementary school students, to do this we thought about the continuing education of teachers regarding the acquisition of new knowledge about the produced studies on reading and writing, the theory of textual genres and systematize practices (didactic sequences). In the first part of the work we use literature to discuss the concepts involved in teacher education and consequently on student learning. After discussing the concept of textual production, we anchored in the theory of genres presented by Marcuschi (2005, 2008, 2011) to reflect on language and social function of genres. To support the work of teachers we prepared a didactic sequence based on Cosson (2014) in which we present systematic activities to promote the written memories of narratives. In the second part we used qualitative research and we use the video for teachers of Indiaroba/SE on the issues studied. The audiovisual material was evaluated by five guest professors and the observations were gathered from a questionnaire that served as collection instrument. The information provided by respondents yield sufficient data to allow us to claim the video is an important support for teacher education. So we can say that the research reached its goal of producing and testing an instrument that we hope to encourage other teachers use it for the sake of expanding their knowledge and improved text production practices in basic education.